Local issues involved in land disputes in relation to oil palm plantation activities: the case of south Sumatera - Amzulian Rifai, (Fakulti Undang - Undang, 2002)

(untitled)
This article analyzes land disputes in South Sumatera. Which arose as a result of oil palm plantation activities. It is important to understand the local issues involved in the – disputes in order to develop a proposal to contend with land problems in South Sumatra. The research conducted for this article revealed that there were five main issues involved in land disputes between the oil palm companies and the landowners in South Sumatra: a) the Abolition of Marga System of local Government, b) the issue of compensation, c) the issue of system plasma, d) issue of human rights violation, and e) the issue of land burning